2022
DOI: 10.1002/jcla.24358
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of serum miR‐320‐3p expression in predicting the prognosis of sepsis‐induced acute kidney injury

Abstract: Background For investigating the expression of miR‐320‐3p in children with sepsis‐induced acute kidney injury (AKI) and its prognostic value. Methods A total of 142 patients were grouped into a survival group (n = 95) and death group (n = 47), which was based on their 28‐day survival. Serum degrees of miR‐320‐3p, neutrophil gelatinase‐associated lipid carrier protein (NGAL) and kidney injury molecule‐1 (KIM‐1) were detected. The Acute Physiology and Chronic Health scoring system Ⅱ (APACHE Ⅱ) marks were recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Bioinformatics analyses have enabled us to understand the molecular mechanisms of AKI occurrence and development and have been used to explore potential targets for AKI diagnosis and treatment. Previous microarray studies have often focused on the role of a single molecule and are largely based on a sepsis-induced AKI model ( Tang et al, 2021 ; Ji et al, 2022 ). However, the vast majority of AKI in clinical work is associated with ischemic–reperfusion injury, and there have been some studies on the gene expression of IRI-AKI ( Wu et al, 2016 ; Wu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics analyses have enabled us to understand the molecular mechanisms of AKI occurrence and development and have been used to explore potential targets for AKI diagnosis and treatment. Previous microarray studies have often focused on the role of a single molecule and are largely based on a sepsis-induced AKI model ( Tang et al, 2021 ; Ji et al, 2022 ). However, the vast majority of AKI in clinical work is associated with ischemic–reperfusion injury, and there have been some studies on the gene expression of IRI-AKI ( Wu et al, 2016 ; Wu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of miR-21-3p, in combination with Scr, Cys-C and kidney injury molecule 1 (KIM-1), were significantly increased in children with sepsis and could predict AKI onset with a sensitivity of 97% and specificity of 91.4% [ 47 ]. Another clinical study revealed that serum miR-320-3p levels were greatly enhanced in children with sepsis-induced AKI, and combining NGAL, KIM-1 and acute physiology and chronic health evaluation (APACHE) II scores could be effective for predicting prognosis in children [ 24 ]. Serum and urinary miR-452 levels increased early after LPS or cecal ligation puncture (CLP) in septic mice, occurring earlier than detectable renal dysfunction or tissue damage.…”
Section: Reviewmentioning
confidence: 99%
“…Clinical trials and animal experiments have demonstrated that modulating miRNA expression is beneficial in several diseases [ 20–23 ]. Some miRNAs are increased in the urine and plasma of patients with septic AKI, suggesting that they might be valuable diagnostic biomarkers [ 24–29 ]. Increasing evidence indicates that miRNAs could be therapeutic targets against septic AKI [ 30–35 ].…”
Section: Introductionmentioning
confidence: 99%